Nutrition and health [ - Carr, Tanya; Descheemaeker, Koen (Blackwell Science, 2002)
Continuing accumulation of scientific evidence demonstrates that nutrition is one of the most important determinants of health for the individual, and that specific nutrition habits of various populations can significantly decrease the overall risk of several chronic diseases. This landmark publication, which contains papers presented at the 1st Nutrition and Health conference, covers the major topics relating to nutritional aspects of health. Chapters within this important book cover vital health issues, including details of the links between diet and cardiovascular disease, obesity, cancer